2012
DOI: 10.2106/jbjs.k.00632
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Techniques Reduce Hospital Stay Following Multilevel Posterior Cervical Spine Surgery

Abstract: Therapeutic Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…For this purpose, we administrated histamine topically using gelfoam on the lesion site after surgery. Gelfoam is an absorbable medical device used as a hemostatic and as a carrier to deliver some agents such as thrombin in the clinic . Topical treatment of gelfoam soaked with histamine makes it more convenient for administration.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we administrated histamine topically using gelfoam on the lesion site after surgery. Gelfoam is an absorbable medical device used as a hemostatic and as a carrier to deliver some agents such as thrombin in the clinic . Topical treatment of gelfoam soaked with histamine makes it more convenient for administration.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,26,27 The efficacy of drains has been challenged for many surgical procedures; however, no study has assessed the necessity of drain use after ACDF. 318,2225 The current study was designed to identify factors that affect drain output after ACDF in order to assist surgeons with the decision of whether or not to place a drain postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Vestergaard et al (2010) indicated that the use of Ostene instead of bone wax could contribute to a reduction in the incidence of sternal dehiscence and chronic inflammation. Cho et al (2012) suggested the application of a thrombinsoaked, absorbable gelatin compressed sponge at the end of multilevel posterior cervical spinal surgery significantly decreased post-operative drain output.…”
Section: Introductionmentioning
confidence: 99%